You can't ignore what you can't separate: the effect of visually induced target-distractor separation on tactile selection. - Wesslein, A; Spence, C; Frings, C (2014)
Research suggests that vision of the body-part that happens to receive a tactile event enhances the processing of this stimulus. However, it would appear that only tactile distractors delivered to visible body-parts are processed up to the level of response selection. Here, we analyze whether vision or higher order cognitive processes influence the processing of tactile distractors. We compared the processing of distractors in a tactile variant of the Eriksen flanker task when the body-parts receiving target and distractor stimuli were separated by different types of barriers. Surprisingly, an impermeable barrier prevented tactile distractors from being processed up to the response level, irrespective of whether the barrier was transparent or opaque. By contrast, when an empty frame was placed between the participant's hands, distractors were processed up to the level of response selection. Hence, higher order cognition (here the visually induced representation of the target-distractor separation) influences the processing of tactile distractors. We discuss these results in the light of related findings from selective reaching experiments as well as in terms of Gestalt grouping.